Transmission of whole body vibration to the lower body in static and dynamic half-squat exercises - Munera Ramirez, Marcela Cristina; Chiementin, Xavier; Bertucci, William; Duc, Sebastien (Taylor and Francis Ltd., 2016)
Whole body vibration (WBV) is used as a training method but its physical risk is not yet clear. Hence, the aim of this study is to assess the exposure to WBV by a measure of acceleration at the lower limb under dynamic and static postural conditions. The hypothesis of this paper is that this assessment is influenced by the frequency, position, and movement of the body. Fifteen healthy males are exposed to vertical sinusoidal vibration at different frequencies (20–60 Hz), while adopting three different static postures (knee extension angle: 180°, 120° and 90°) or performing a dynamic half-squat exercise. Accelerations at input source and at three joints of the lower limb (ankle, knee, and hip) are measured using skin-mounted accelerometers. Acceleration values (g) in static conditions show a decrease in the vibrational dose when it is measured at a more proximal location in the lower extremity. The results of the performed statistical test show statistically significant differences (p < 0.05) in the transmissibility values caused by the frequency, the position, and to the presence of the movement and its direction at the different conditions. The results confirm the initial hypothesis and justify the importance of a vibration assessment in dynamic conditions.

La vibración de cuerpo entero (WBV) se utiliza como método de entrenamiento, pero su riesgo físico aún no está claro. Por lo tanto, el objetivo de este estudio es evaluar la exposición al WBV mediante una medida de aceleración en el miembro inferior en condiciones posturales dinámicas y estáticas. La hipótesis de este trabajo es que esta evaluación está influenciada por la frecuencia, posición y movimiento del cuerpo. Quince varones sanos están expuestos a vibraciones sinusoidales verticales a diferentes frecuencias (20-60 Hz), mientras adoptan tres posturas estáticas diferentes (ángulo de extensión de la rodilla: 180 °, 120 ° y 90 °) o realizan un ejercicio dinámico de media sentadilla. Las aceleraciones en la fuente de entrada y en tres articulaciones de la extremidad inferior (tobillo, rodilla y cadera) se miden utilizando acelerómetros montados en la piel. Los valores de aceleración (g) en condiciones estáticas muestran una disminución en la dosis vibratoria cuando se mide en una ubicación más próxima en la extremidad inferior. Los resultados de la prueba estadística realizada muestran diferencias estadísticamente significativas (p <0.05) en los valores de transmisibilidad causados ​​por la frecuencia, la posición y la presencia del movimiento y su dirección en las diferentes condiciones. Los resultados confirman la hipótesis inicial y justifican la importancia de una evaluación de vibraciones en condiciones dinámicas.
Keywords: Vibración; Aceleracion - Velocidad; Ejercicio - Ejercicios de piernas; Circuito de entrenamiento; Circuit training; Articulaciones - Rango de movimiento; Joints - Range of motion; Ejercicio isométrico; Isometric exercise; Vibration exercise; Acceleration; Training; Ejercicio de vibración; Aceleración; Capacitación